2014
DOI: 10.1111/1467-6427.12063
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the working alliance in family therapeutic home‐based treatment of multi‐problem families

Abstract: Families with a low socioeconomic status play an increasingly significant role in health services, research and social policy. The present outcome research study is a pre/post naturalistic study of home-based therapeutic work with multi-problem families (MPF), as conducted by Therapeutisch Ambulante Familenbetreung, an integrative family therapy with a structure-related, mentalization-based, psychoanalytic orientation. With a mean treatment duration of 75.7 weeks, 379 families showed significant psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 49 publications
0
32
0
2
Order By: Relevance
“…Therefore, a fine-tuning of each individual change process according to the present state of the therapeutic relationship and adapting interventions accordingly might help to increase the willingness of patients and their ability to collaborate. Therapists’ activities in fostering the collaboration on goals is influenced bidirectional by a number of further relevant evidence-based technical adaptive features in the treatment of therapy in treatment of MPF: Handling RRPs (rupture repair processes) and thereby fostering the development of the therapeutic bond, emphasizing change by adaptive therapist activity (flexibility, availability and treatment intensity), setting rules and boundaries (consensus on task), processing maladaptive intrapsychic and interpersonal thoughts, behavior and parenting (Lebow, 2005; Bachler et al, 2014); and, as our data show, improving outcome expectations (hope) by encouraging patients and by supporting them in solving adversities within the family. In particular, differentiating “stable collaboration” (low, medium high stable) from improving and deteriorating collaboration helps explaining the therapeutic outcome and offers a valid approach to everyday practice.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a fine-tuning of each individual change process according to the present state of the therapeutic relationship and adapting interventions accordingly might help to increase the willingness of patients and their ability to collaborate. Therapists’ activities in fostering the collaboration on goals is influenced bidirectional by a number of further relevant evidence-based technical adaptive features in the treatment of therapy in treatment of MPF: Handling RRPs (rupture repair processes) and thereby fostering the development of the therapeutic bond, emphasizing change by adaptive therapist activity (flexibility, availability and treatment intensity), setting rules and boundaries (consensus on task), processing maladaptive intrapsychic and interpersonal thoughts, behavior and parenting (Lebow, 2005; Bachler et al, 2014); and, as our data show, improving outcome expectations (hope) by encouraging patients and by supporting them in solving adversities within the family. In particular, differentiating “stable collaboration” (low, medium high stable) from improving and deteriorating collaboration helps explaining the therapeutic outcome and offers a valid approach to everyday practice.…”
Section: Resultsmentioning
confidence: 99%
“…SSE-TAF (social self-sufficiency) is a validated (interrater reliability 0.73) part of the TAF documentation (TAF-DOK) and tries to document the social self-preservation ability of the family with one item ( Bachler et al, 2014 ). The SSE TAF measures the ability to work and is a is based on a 5-tiered Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological data show that up to 20% of children and adolescents show mental disorders ( Belfer , 2008 ). The prevalence of neglect, maltreatment, deprivation in childhood in Germany is estimated with about 10–15% ( Reichl et al, 2014 ), higher rates were found in multi problem families (MPF; Belfer, 2008 ), which leads to an increased risk of vulnerability for children ( Egle et al, 2004 ; Bachler et al, 2014 ). High-risk families not only meet many criteria of family adversity indices, but also show low treatment compliance and low relational functioning of the families ( Bachler et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This poses a serious challenge for the development of successful therapeutic principles in the treatment of MPFs (Bachler et al, 2017). For a long time, it was assumed that parents and adolescents in MPFs were unable or unwilling to collaborate in a goal-directed manner; they were referred to as "unwilling, involuntary or mandated clients" (Bachler et al, 2016). In the categorization of Friedlander et al (2011), who identified four groups of individuals or families in psychotherapy ("customers, " "plaintiffs, " "visitors, " and "hostages"), MPFs are found in the "plaintiffs, " "visitors, " and "hostages" categories.…”
Section: Treatment Of Mpfs Familiesmentioning
confidence: 99%